Filament Materials Screening for FDM 3D Printing by Means of Injection‐Molded Short Rods. Issue 12 (19th October 2018) - Jin, Minde; Giesa, Reiner; Neuber, Christian; Schmidt, Hans‐Werner
Abstract: A miniature small‐scale material processing and testing approach is developed as a screening method to evaluate polymer materials for fused deposition modeling (FDM). This method is suitable for a small material input of less than 10 g using a mini compounder in combination with an injection molding machine to manufacture short rods usable as FDM feedstock material. Compared with conventional continuous filament extrusion, where the amount of raw material required is around 1–5 kg, time and material consumption are both significantly reduced for the investigation of FDM filament materials or formulations. In order to demonstrate this method, three different polypropylene grades are processed into rods and compared to commercially available continuous filaments. In addition to warp deformation, interlayer bonding properties are also measured on test specimens punched out of FDM‐printed square tubes. The presented rod preparation and square tube printing offer fast and efficient material screening and optimization for new FDM material development. Abstract : Small‐scale material screening for fused deposition modeling (FDM) 3D printing by using injection molded short rods allows FDM printing in the same way as feeding continuous FDM filaments. By applying this method, material, time, and cost are minimized for the screening and investigation of FDM materials in the early development stage.